Upaya Optimasi Pertumbuhan dan Hasil Panen Cabai Keriting di Tanah Berpasir Dengan Pemanfaatan Pupuk Organik Cair dan Yellow Trap - Amar Sidiq, Muhammad; Hidayati, Nurul; Arfianto, Fahruddin (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
This study evaluates the effectiveness of integrating liquid organic fertilizer (LOF) and yellow traps on the agronomic performance of curly chili (Capsicum annuum L.) in marginal sandy soil. Conducted in Palangka Raya, the research employed a split-plot design with three replications, where yellow traps served as the main plot and LOF dosages (0, 9, 18, and 27 ml/plant) were designated as sub-plots. Statistical analysis revealed that neither the interaction between treatments nor the individual application of yellow traps had a significant impact on most growth variables. However, LOF application within the range of 18–27 ml significantly enhanced stem diameter at 49 days after planting (DAP) and the total number of fruits per plant. Conversely, parameters such as plant height, fruit biomass, and damage intensity showed no substantial differences across treatments. The physiological response of the plants was heavily influenced by environmental dynamics, particularly rainfall intensity and the low nutrient retention capacity of sandy soil. It is concluded that the combination of yellow traps and an 18 ml LOF dosage represents the most optimal strategy for supporting curly chili productivity under these specific environmental conditions.